PERANAN ROH KUDUS DALAM KEHIDUPAN ORANG PERCAYA DI ERA GENERASI Z - Like, Like (Shift Key : Jurnal Teologi dan Pelayanan, 2022)
From the time of the Old Testament, the New Testament, the Generation of War, even to Generation Z as believers really need the Holy Spirit. The purpose of this study is to describe the gift of the Holy Spirit and His role in the lives of believers in the era of generation Z. The approach used in this research is the literature method with a descriptive qualitative approach. The conclusion is that the gift of the Holy Spirit and His role are very important in the lives of believers in the Era of Generation â€œZâ€, namely the digital technology generation.